Validation of the Foot and Ankle Outcome Score for Hallux Rigidus. Issue 1 (February 2016) - Hogan, MaCalus V.; Mani, Sriniwasan B.; Chan, Jeremy Y.; Do, Huong; Deland, Jonathan T.; Ellis, Scott J.
Background: There is a clear call for improved patient-centered outcomes. The Foot and Ankle Outcome Score (FAOS) is a region-specific patient-reported measure that has been validated for a number of foot and ankle diagnoses, but not hallux rigidus. Questions/Purposes: The aim of this study was to validate the FAOS in patients with hallux rigidus. Methods: From 2007 to 2013, 211 patients with hallux rigidus (HR) were included in the study. For the construct validity portion of the study, 125 patients completed a Short-Form 12 (SF-12) and FAOS survey. Forty additional HR patients were prospectively given questionnaires to assess the relevance of each FAOS question as it pertained to their HR. Reliability was assessed in 36 HR patients via administration of a second FAOS an average 1 month following the first. In 55 patients, preoperative and postoperative FAOS scores were compared to determine responsiveness. Results: All FAOS subscales demonstrated moderate correlation coefficients with the physical functioning, role physical, bodily pain, and physical health component scores of the SF-12, with all subscales demonstrating poor correlation with the SF-12 mental health-related domains. Content validity was high for all FAOS scores, with the exception of the daily activities subscale. All subscales achieved acceptable test–retest reliability with correlation coefficients of ≥0.72. Furthermore, all subscales were rated as responsive to change in postoperative patients ( p < 0.001). Conclusion: This study demonstrates the acceptable construct and content validity, reliability, and responsiveness of the FAOS for hallux rigidus. Due to its broad applicability and proven validation across multiple foot and ankle pathologies, the FAOS represents a patient-centered outcome measure that can be reliably used for the assessment of patients with hallux rigidus.